2016
DOI: 10.1080/19338244.2016.1222346
|View full text |Cite
|
Sign up to set email alerts
|

Measuring extent of surface contamination produced by the handling of antineoplastic drugs in low- to middle-income country oncology health care settings

Abstract: Antineoplastic drugs are known to cause detrimental effects to health care workers who are exposed through work tasks. Environmental monitoring studies are an excellent approach to measure the extent of surface contamination produced by the handling of antineoplastic drugs in the workplace and to assess the potential for occupational exposures in oncology health care settings. The main aim of the study was to establish the extent of surface contamination produced by the handling of antineoplastic drugs in a li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
5
10
0
Order By: Relevance
“…If we compare our range of surface CP contamination (< LOQ−208.85 ng/cm 2 ), with the literature, which reported concentrations from < LOQ to 14 ng/cm 2 , substantially higher contamination was observed in our study ( 12 , 25 , 27 , 32 35 ). Müller-Ramírez et al ( 14 ) reported values ranging from 0.3 to 168.9 ng/cm 2 , which is more in line with our results, while only one study reported ranges exceeding ours with contamination up to 21,300 ng/cm 2 ( 36 ). This concentration was found on a phone in a room next to the preparation room and was probably caused by touching the phone with contaminated gloves and inadequate cleaning.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…If we compare our range of surface CP contamination (< LOQ−208.85 ng/cm 2 ), with the literature, which reported concentrations from < LOQ to 14 ng/cm 2 , substantially higher contamination was observed in our study ( 12 , 25 , 27 , 32 35 ). Müller-Ramírez et al ( 14 ) reported values ranging from 0.3 to 168.9 ng/cm 2 , which is more in line with our results, while only one study reported ranges exceeding ours with contamination up to 21,300 ng/cm 2 ( 36 ). This concentration was found on a phone in a room next to the preparation room and was probably caused by touching the phone with contaminated gloves and inadequate cleaning.…”
Section: Discussionsupporting
confidence: 92%
“…For IFO we observed concentrations ranging from < LOQ up to 23.45 ng/cm², which is in line with concentrations (0.08-15.7 ng/cm²) reported by Müller-Ramírez et al (14). Other studies reported substantially lower contamination (12,25,33,35), or considerably higher contamination (< LOQ−95 ng/cm²) (32,37).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…To achieve the 2030 target, implementation and scale‐up require recognizing the needs and capacities of health professionals, including nurses. Nurses in LMIC are frequently exposed to occupational hazards due to work environments that lack the required resources for safe care, such as personal protective equipment (PPE) for handling chemotherapy . The absence of specialized education, coupled with frequent rotation of trained staff, leaves nurses ill‐equipped to safely deliver care for children/adolescents with cancer .…”
Section: International Society Of Paediatric Oncology (Siop) Pediatrimentioning
confidence: 99%
“…Nurses in LMIC are frequently exposed to occupational hazards due to work environments that lack the required resources for safe care, such as personal protective equipment (PPE) for handling chemotherapy. 6,7 The absence of specialized education, coupled with frequent rotation of trained staff, leaves nurses ill-equipped to safely deliver care for children/adolescents with cancer. 8 The Nurse Specialists of the Global Initiative for Childhood Cancer join public calls for all nurses (particularly those in resourcelimited settings), to be provided with protection when managing hazardous drugs as well as oncology specialization training to ensure optimal nursing care.…”
mentioning
confidence: 99%